On some advantages and disadvantages of the legislative regulation of intentional substitution of a child in the Criminal Code of the Republic of Belarus - Laptsevich, Irina I. (Journal of the Belarusian State University. Law, 2019)
Some theoretical criminal law aspects of the deliberate substitution of a child are analyzed in the context of determining the place of this corpus delicti in the system of norms of the Criminal Code of the Republic of Belarus, of its immediate object and degree of public danger. The author by means of historical analysis and research of the objects of the deliberate substitution of the child and abduction of a person, concludes that the legislator has a reasonable approach to the division of these norms of criminal law. Proposals on the direction of improving the sanctions of art. 180 of the Criminal Code of the Republic of Belarus are submitted.